Biopuncture, A Multitarget Therapy in the Treatment of Individuals with Knee Osteoarthritis: state of the art - Pedro Iván Arias-Vázquez; María Antonieta Ramírez-Wakamatzu; Blanca Gabriela Legorreta-Ramírez (Korean Pharmacopuncture Institute, 2024)
Background: Biopuncture is a described technique that consists in subcutaneous injection of antihomotoxic drugs (homeopathic compounds) mixed with other substances such as local anesthetics or dextrose; This has been proposed as a treatment option to reduce musculoskeletal pain in various locations, including knee osteoarthritis.Objectives: The objective of this manuscript was to carry out a comprehensive review of the published information on the use of Biopuncture in patients with knee osteoarthritis.Methods: A scientific search was performed using online databases following the terms (Biopuncture) and (Knee Osteoarthritis) to identify scientific manuscripts that were related to the use of Biopuncture in the treatment of individuals with knee osteoarthritis.Results: With the information found, a theoretical framework was integrated that describes the components of Biopuncture, its mechanism of action and practical topics for the application of the technique.Conclusion: Biopuncture appears to be a potential, simple and low-risk therapeutic strategy in the treatment of knee osteoarthritis, which is applied through periarticular subcutaneous injections, with multitarget mechanisms of action at various physiopathological levels such as the modulation of the inflammatory process, decreased peripheral sensitization, and stimulation of antidegenerative and trophic mechanisms. Perhaps it can be part of the integrative treatments for knee osteoarthritis.